Two new species of Cosmolaelaps Berlese (Acari: Laelapidae) from Sri Lanka - Joharchi, Omid; Ermilov, Sergey G.; Khaustov, Alexander A. (Zootaxa, 2020)
Two new species of mites in the genus Cosmolaelaps (Laelapidae) are described from specimens collected from soil-litter in Sri Lanka—C. ceylonensis sp. nov. and C. trichiurus sp. nov. The genus Cosmolaelaps is reported for the first time from Sri Lanka.